Comparative evaluation of low-cost Macintosh video laryngoscope with conventional Macintosh laryngoscope: A randomized controlled trial - Popli, Shilpa; Kumar, Amit; Manohar, Manisha; Popli, Riya; Popli, Bhuvan Priyanshu; Anshul, (Asian Journal of Medical Sciences, 2023)
Background: The prohibitive costs of commercially available video laryngoscopes often limit the adoption of this technique for routine airway management in economically weak countries. It has not yet been determined whether cost-effective adjustments improve intubation success rates to the required level of competence. Aims and Objectives: To compare a custom-made low-cost Macintosh video laryngoscope with a standard Macintosh laryngoscope (ML). The primary objectives were to compare laryngoscopy time, intubation time, and procedure time. The secondary objectives were to compare Cormack–Lehane grading (CL), rate of successful tracheal intubation, number of attempts for successful intubation, need for backward, upward, and rightwars pressure (BURP), and perceived ease of intubation based on intubation difficulty scale (IDS). Materials and Methods: Forty adults posted for elective surgery under general anesthesia were randomized to Group (intubated with a standard ML) and Group (intubated with a custom-made, Macintosh video laryngoscope [CMVL]). Results: The laryngoscopy time was 7.5±2.04 s in Group CMVL and 5.85±1.26 s in Group ML (P=0.0039). The intubation time was 7.95±1.73 s in Group CMVL and 7.75±2.35 s in Group ML (P=0.7615). The procedure time was 15.45±2.96 s in group CMVL and 13.6±2.99 s in group ML (P=0.0571). The Group CMVL had significantly lower laryngoscopy time than Group ML. In terms of IDS, CL grading, number of successful intubation, and BURP required both groups were comparable. Conclusion: Both the laryngoscopes provide more or less similar results concerning all the intubation parameters studied in normal airway scenarios. Thus, emphasizing that the mere presence of a camera alone does not improve the intubation characteristics in normal airway patients.